Insights into Stability and Selective Agglomeration in Binary Mixtures of Colloids: A Study on Gold Nanoparticles and Ultra-Small Quantum Dots - Azita Rezvani; Alexander Kichigin; Benjamin Apeleo Zubiri; Erdmann Spiecker; Doris Segets (Powders)
Controlling the stability of colloidal nanoparticles in multicomponent systems is crucial for advancing formulations and separation processes. This study investigates the selective agglomeration approach for binary colloidal mixtures, providing both fundamental insights into stability/agglomeration mechanisms and a scalable separation strategy. First, we established a binary model system comprising gold nanoparticles (Au NPs) and ZnS quantum dots (QDs) to assess interparticle interactions. UV-visible spectroscopy revealed that impurities released from ZnS QDs, particularly thiol-based ligands and unbound Zn ions, triggered the aggregation of Au NPs depending on their surface stabilizers. Functionalization of Au NPs with bis(p-sulfonatophenyl) phenylphosphine (BSPP) significantly enhanced colloidal stability, with unpurified BSPP-functionalized Au NPs exhibiting superior resistance to agglomeration. Building on these insights, we applied selective agglomeration to separate a complex colloidal system consisting of InP/ZnS core–shell QDs and ZnS byproducts, a critical challenge in QD synthesis that is particularly relevant for post-processing of samples that originate from large-scale flow synthesis. By systematically tuning the ethanol concentration as a poor solvent, we successfully achieved composition-dependent fractionation. Optical and spectroscopic analyses confirmed that coarse fractions were enriched in InP/ZnS QDs, while fines fractions mainly contained pure ZnS QDs, with absorption peaks at 605 nm and 290 nm, respectively. Photoluminescence spectra further demonstrated a redshift in the coarse fractions, correlating with an increase in particle size. These results underscore the potential of selective agglomeration as a scalable, post-synthesis classification method, offering a framework for controlling stability and advancing post-synthesis separation strategies in colloidal multicomponent systems.